History and Future Perspectives on the Discipline of Quantitative Systems Pharmacology Modeling and Its Applications - Azer, Karim; Kaddi, Chanchala D.; Barrett, Jeffrey S.; Bai, Jane P. F.; McQuade, Sean T.; Merrill, Nathaniel J.; Piccoli, Benedetto; Neves-Zaph, Susana; Marchetti, Luca; Lombardo, Rosario; Parolo, Silvia; Immanuel, Selva Rupa Christinal; et al. (Frontiers in Physiology, 2021)
Mathematical biology and pharmacology models have a long and rich history in the fields of medicine and physiology, impacting our understanding of disease mechanisms and the development of novel therapeutics. With an increased focus on the pharmacology application of system models, and advances in data science spanning mechanistic and empirical approaches, there is a significant opportunity and promise to leverage these advancements to enhance the development and application of the systems pharmacology field. In this paper, we will review milestones in the evolution of mathematical biology and pharmacology models, highlight some of the gaps and challenges in developing and applying systems pharmacology models and provide a vision for an integrated strategy that leverage advances in adjacent fields to overcome these challenges.